Glanzmann Thrombasthenia: Perspectives from Clinical Practice on Accurate Diagnosis and Optimal Treatment Strategies - Mathews, Natalie (J Blood Med, 2021)
Glanzmann thrombasthenia (GT) is a rare autosomal recessive disorder of fibrinogen-mediated platelet aggregation due to a quantitative or qualitative deficit of the α(IIb)β(3) integrin at the platelet surface membrane resulting from mutation(s) in ITGA2B and/or ITGB3. Patients tend to present in early childhood with easy bruising and mucocutaneous bleeding. The diagnostic process requires consideration of more common disorders of haemostasis and coagulation prior to confirming the disorder with platelet light transmission aggregation, flow cytometry of CD41 and CD61 expression, and/or exon sequencing of ITGA2B and ITGB3. Antifibrinolytic therapy, recombinant activated factor VII, and platelet transfusions are the mainstay of therapy, although the latter may trigger formation of anti-platelet antibodies in GT patients and inadvertent platelet-refractory disease. The management of these patients therefore remains complex, particularly in the context of trauma, labour and delivery, and perioperative care. Bone marrow transplantation remains the sole curative option, although the venue of gene therapy is being increasingly explored as a future alternative for definitive treatment of GT.